2021
DOI: 10.3390/cancers13010159
|View full text |Cite
|
Sign up to set email alerts
|

Ways into Understanding HIF Inhibition

Abstract: Hypoxia is a key characteristic of tumor tissue. Cancer cells adapt to low oxygen by activating hypoxia-inducible factors (HIFs), ensuring their survival and continued growth despite this hostile environment. Therefore, the inhibition of HIFs and their target genes is a promising and emerging field of cancer research. Several drug candidates target protein–protein interactions or transcription mechanisms of the HIF pathway in order to interfere with activation of this pathway, which is deregulated in a wide ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 131 publications
0
17
0
Order By: Relevance
“…Below, we briefly report the main aspects of the inhibition strategy and examples of chemical agents used. For a more detailed discussion about drugs, targets, and mechanisms, more specific reviews should be consulted [ 121 , 122 , 123 ].…”
Section: Targeting Hif-1 In Cancer Therapymentioning
confidence: 99%
“…Below, we briefly report the main aspects of the inhibition strategy and examples of chemical agents used. For a more detailed discussion about drugs, targets, and mechanisms, more specific reviews should be consulted [ 121 , 122 , 123 ].…”
Section: Targeting Hif-1 In Cancer Therapymentioning
confidence: 99%
“…Several compounds have been studied as inhibitors of HIF- α transcription, translation, and protein stabilisation (Ref. 116). Of these, some, such as SN-38 (the active metabolite of irinotecan), alongside its well-established radiosensitiser effect as a topoisomerase I inhibitor, can also lead to increased radiosensitivity through inhibiting radiation-induced HIF-1 α in colorectal cancer (Ref.…”
Section: Targeting Of Hypoxia-mediated Signalling Reprogramming As Ra...mentioning
confidence: 99%
“…PX-478 decreases HIF-1 α levels by inhibiting HIF-1 α translation, as well as inhibiting de-ubiquitination leading to HIF-1 α protein degradation (Ref. 116). Palayoor et al have shown a potential role for PX-478 as a clinical radiation enhancer in prostate carcinoma cells (Ref.…”
Section: Targeting Of Hypoxia-mediated Signalling Reprogramming As Ra...mentioning
confidence: 99%
“…The potential for the development of adverse and unanticipated effects is high due to the intertwined nature. Regarding HIF inhibitors, the use of many is dampened by their off-target effects, affecting different pathways in DNA replication, cell division, or cell signaling [220]. HMG-CoA reductase inhibitors have been hypothesized to influence intracellular signaling pathways and immune processes [221,222]; their several pleiotropic off-target effects have been investigated in cancer therapy by delaying DNA repair and inducing senescence [223].…”
Section: Hormones and Other Pharmacological Agentsmentioning
confidence: 99%